PROJETO COMQUISTA - Comunidades Quilombolas de Vitória da Conquista: Avaliação do Consumo de Frutas, Legumes e Verduras e das Possibilidades do uso do Índice de Massa Corporal Autorreferido - Poliana Cardoso Martins (2014)
This thesis is part of a population-based survey called Project COMQUISTA Quilombo Communities of Vitoria da Conquista: Evaluation of health and its determinants. It is composed of two articles that examined the possibility of using autoreferridas anthropometric measurements and factors associated with adequate consumption of fruits and vegetables (FLV) factors. Sample of 797 individuals aged 18 years or more. The first study aimed to assess the validity of using self-reported anthropometric data for the diagnosis of nutritional status. We obtained the proportion of individuals who knew the anthropometric measures. For the analysis of agreement between those who reported measures were calculated: differences between means, the intraclass correlation coefficient (ICC), kappa statistic, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Also Obtained Bland & Altman. They knew not report information on weight and height 58.5% of respondents. The weight was the best-known measure compared to the others. The magnitude of the difference between the means was small for weight, height and body mass index (0.43 kg, 0.31 cm, 0.32 kg/m2, respectively), shown good agreement intrapares and a tendency to overestimation of the measures. The ICC for weight, height and BMI were, respectively, 0.96; 0.60 and 0.53. The kappa statistic indicated good agreement for the strata evaluated. General measures of sensitivity, specificity, PPV and NPV were 84.2%, 82%, 90.7% and 71.3% respectively. Presented in the lower accuracy measures the elderly, people with less than 4 years of schooling and are not often weigh. The cautious use of self-reported measures in epidemiological studies in rural populations is recommended. The second paper aimed to evaluate the appropriate FV intake through the description and analysis of prevalence and associated factors. An estimate of the prevalence of consumption of fruits and vegetables with the 95% confidence interval for proportions was taken. To identify factors associated with adequate FV intake factors, we conducted a univariate analysis. We used Poisson regression with robust variance was adopted and the hierarchical entry of variables into blocks. Association with the presence of refrigerators at home, schooling, frequent consumption of meat and chicken Adequate consumption, ie, five or more times per day was reported by 26.1% of respondents were hierarchical multivariate analysis, there was and milk, the habit of removing the visible fat from the meat, the practice of physical activity and daily consumption of beans, and nutritional status. Note-if a suitable low fruit and vegetable intake and socioeconomic and behavioral factors have a significant influence on FV intake, and are subject to intervention, may contribute to the adoption of healthy eating habits.